Preparation and activity of copper-gallium nanocomposite catalysts for carbon dioxide hydrogenation to methanol - Hengne, Amol M.; Yuan, Ding Jier; Date, Nandan S.; Saih, Youssef; Kamble, Sanjay P.; Rode, V. Chandrashekhar; Huang, Kuo-Wei (Industrial & Engineering Chemistry Research, 2019)
Copper (Cu) nanocomposite catalysts with gallium (Ga) and aluminum (Al) were prepared using the simultaneous coprecipitation digestion method. The catalysts were characterized by N-2 adsorption, N2O titration, XRD (X-ray diffraction), H-2-TPR (H-2 temperature-programmed reduction), XPS (X-ray photoelectron spectroscopy), and CO2-TPD (CO2 temperature-programmed desorption) techniques, and CO2 hydrogenation to methanol synthesis was performed. The use of Ga in Cu catalysts enhanced the weak basic sites more than the Cu catalysts with Al. With the CuGa nanocomposite formation, the catalyst showed a sequential reduction of CuO, for example, Cu+2 to Cu+ to Cu-0, and the Cu surface area was also high in comparison with CuAl. These findings confirmed that both the Cu surface area and CuO reducibility in the catalyst helped to boost the conversion of CO2, whereas selectivity to methanol was associated with the basicity of the catalyst. CuAl catalysts showed very poor selectivity to methanol despite CO formation, which could be due to the weak interaction of the CuAl nanocomposite catalysts compared to the CuGa nanocomposite catalysts.

Selective hydrogenation of 5-HMF to 2,5-DMF over a magnetically recoverable non-noble metal catalyst - Solanki, Bhanupratap Singh; Rode, V. Chandrashekhar (Green Chemistry, 2019)
A non-noble bimetallic catalyst Cu-Fe (1 : 2) was magnetically recoverable, highly selective and efficient for 5-(hydroxymethyl) furfural (5-HMF) hydrogenation to 2,5-dimethyl furan (DMF). The structure-activity correlation was established by characterising the prepared catalyst by XRD, XPS, TEM, ESEM, BET surface area, N-2-adsorption, NH3-TPD, pyridine-IR and H-2-TPR measurements. The high catalytic efficiency was attributed to the oxophilic nature and Lewis acidity of Fe, whereas the selectivity towards DMF was attributed to the Bronsted acidity of CuO and its affinity towards the C-O bond which was further confirmed by NH3-TPD and Py-IR analyses. XPS and XRD revealed the presence of Cu/CuFe2O4 species which catalyzed the hydrogenolysis pathway. TEM and SEM images evidenced the presence of a Cu-Fe nanomorph in which Cu/CuFe2O4 was present. The size of the Cu-Fe nanomorph was found to be between 15.4-17.6 nm. Under the optimised reaction conditions, the highest conversion of 97% and selectivity of 93% were achieved.

Enhanced anisole hydroxylation over a hierarchical micro/mesoporous TS-1 catalyst - Patil, Chetana R.; Niphadkar, Prashant; Kamble, Sanjay P.; Rode, V. Chandrashekhar (New Journal of Chemistry, 2022)
Hierarchical TS-1 materials were synthesized using hydrothermal synthesis and a post modification technique through desilication. They were evaluated for hydroxylation of anisole to produce industrially important chemicals, o-methoxyphenol (OMP) and p-methoxyphenol (PMP). The detailed characterization of the prepared catalysts, such as morphology, structure, nature of Ti and surface area were obtained by SEM, HR-TEM, XRD, UV-VIS spectroscopy and the BET technique. The effects of various operational parameters such as substrate/H2O2 molar ratio, reaction temperature, catalyst concentration and solvent effect on the hydroxylation of anisole have been studied in detail. The microporous TS-1 catalyst showed 32% anisole conversion with 34% selectivity to PMP, while the micro/mesoporous DTS-1 catalyst showed enhanced activity for anisole hydroxylation, i.e. 54% conversion with 55% selectivity towards PMP. The increased framework Ti and improved accessibility of the active sites located in the channels of DTS-1, which permit the mass transfer of reactants, transition states and products from the mesopores of DTS-1, were responsible for the enhanced catalytic activity and selectivity towards p-methoxyphenol.

Highly efficient chemoselective hydrogenation of 5-HMF to BHMF over reusable bimetallic Pd-Ir/C catalyst - Ratrey, Geetanjali; Solanki, Bhanupratap S.; Kamble, Sanjay P.; Rode, V. Chandrashekhar (ChemistrySelect, 2022)
Catalytic synergism was observed for a bimetallic Pd-Ir catalyst supported on activated carbon for chemoselective hydrogenation of 5-hydroxymetahyl furfural (5-HMF) to 2, 5-(bishydroxymethyl) furan (BHMF) with complete conversion and 97 % selectivity under very mild reaction conditions. The structural characterization like XRD, N-2 sorption, FE-SEM and TEM suggested formation of fine nanoparticles (1.95-3.08 nm) having very higher surface area, uniform distribution and mesoporous nature of the material. XPS spectra and Pyridine-IR spectroscopy revealed formation of Pd-PdO and Ir/IrO2/IrO3 interface on the catalytic surface along with strong Bronsted acidic sites which were responsible for high efficiency of catalyst at 80 degrees C, 100 psig H-2 pressure at 5-HMF/Catalyst=20 and within 2.5 h of reaction time. A plausible reaction mechanism is also elucidated based on structure activity correlation.
Keywords: 5-HMF; Carbon; Catalytic synergism; Selective hydrogenation; Valorization

Integrated chemo and bio-catalyzed synthesis of 2,5-furandicarboxylic acid from fructose derived 5-hydroxymethylfurfural - Parate, Roopa D.; Dharne, Mahesh S.; Rode, V. Chandrashekhar (Biomass & Bioenergy, 2022)
Biomass being a renewable source of energy, has emerged as an attractive target for manufacturing valuable products. These possibilities can be explored to meet the current need for degradable plastic, 2,5-furandicarboxylic acid (FDCA). Integration of chemical and biological approaches for direct biomass conversion into FDCA was evaluated in this study. 5-hydroxymethylfurfural (5-HMF) was chemo-catalytically obtained from fructose using recyclable amberlyte IR-120 as a catalyst with >98% purity. Klebsiella oxytoca NCIM 2694 bacterial strain showed the potential of converting 98% of 5-HMF into FDCA with 58% selectivity at 96 h. With optimized conditions of pH 7, 37 degrees C, 2 g whole cells, we reported 99% 5-HMF conversion to FDCA with 95% selectivity at 72 h and 2667 mg L-1 yield, with 39 mg L-1 h-1 productivity. This is the highest yield obtained with the substrate concentration as high as 3000 mg L-1 reported till date. While the bacterial tolerance to 5-HMF observed was for the highest 5-HMF concentration of 4000 mg L-1, with 99% conversion however, compromising the FDCA yield to 2447 mg L-1 and 32 mg L-1 h-1 productivity. Atom economy of 85% and E factor of 17.71 g g-1 was obtained as a measure of its efficiency and sustainability of the process. The developed process will decrease the cost by excluding any extra nutrient supplement, complete substrate utilization, highest FDCA selectivity/productivity and higher tolerance by K. oxytoca, sequentially catalyzing the oxidations by a single route for FDCA synthesis from renewables.
Keywords: biocatalysis; Biodegradable polyester; Biomass; Platform chemical; Sustainability metrics

Synthesis of indeno-[1,2-b]-quinoline-9,11(6H,10H)-dione and 7,7-dimethyl-10-aryl-7,8-dihydro-5H-indeno[1,2-b]quinoline-9,11(6H,10H )-dione derivatives in presence of heterogeneous Cu/zeolite-Y as a catalyst - Dhengale, Shankar D.; Rode, V. Chandrashekhar; Kolekar, Govind B.; Anbhule, V. Prashant (RSC Advances, 2022)
A simple method for the synthesis of indeno-[1,2-b]-quinoline-9,11-(6H,10H)-dione derivatives and 7,7-dimethyl-10-aryl-7,8-dihydro-5H-indeno[1,2-b]quinoline-9,11(6H,10H )-diones through the reaction of aromatic aldehydes, indan-1,3-dione, dimedone, and p-toluidine/ammonium acetate in the presence of heterogeneous CuO supported on a zeolite-Y catalyst has been investigated in ethanol under reflux conditions. By this method, the reaction time has been reduced, giving an excellent yield of the product. The catalyst was prepared by a hydrothermal method followed by a wet impregnation method. The catalyst had shown Bronsted acid sites and Lewis acid sites. The used catalyst could be actively recycled with a marginal decrease in yield up to five recycles. The prepared catalyst was characterized by FT-IR, pyridine FT-IR, XRD, SEM, EDS, XPS, TEM, and BET surface area analysis. The synthesized compounds were characterized by FT-IR, H-1 NMR, C-13 NMR and GC-MS spectroscopy.